The quality of higher education and its relationship with the management of organizational change among the teacher the administrator - Lahmidi, Adel (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
The study of quality within higher education institutions is one of the topics that has gained a lot of luck recently due to its great importance, especially in the field of providing the highest-level services that live up to the requirements of the current society. This is what this study aimed at by identifying the relationship between the quality of higher education and the management of organizational change by the administrative professor, by identifying the dimensions of education quality and the extent of the difference in both variables. For all the administrative professors at the university, the following questions were asked: - Is there a correlation between the quality of inputs and the management of organizational change for the administrative professor? - Is there a correlation between the quality of operations and the management of organizational change for the administrative professor? - Is there a correlation between the quality of outputs and the management of organizational change for the administrative professor? In order to test the hypotheses of the study, the methodological procedures of relying on the analytical descriptive approach were followed because it is most appropriate to address the subject of our study. The results of the study indicated that there is a strong, positive, statistically significant correlation relationship in light of the values of : inputs, processes, and outputs, and this means that all partial hypotheses have been fulfilled. Higher education and management of organizational change.